Hydrochar from sugarcane industry by-products: assessment of its potential use as a soil conditioner by germination and growth of maize - Fregolente, Laís G. [UNESP] (2021)
Background: Hydrothermal carbonization (HTC) is a thermochemical process to convert biomass in carbon-rich materials (hydrochar). The use of sugarcane industry by-products in HTC has been evaluated, generating a hydrochar rich in nutrients, which could be used as a soil conditioner. We raised the hypothesis that the application of hydrochar in soil can improve its nutrient characteristics, bringing a better environment and favouring plant growth, expecting a development similar to that one observed in anthropogenic soils. Results: Germination studies were performed expecting a species-dependent response, using maize and tomato seeds, whose development was assessed in two soluble fractions obtained from hydrochar aiming to evaluate different rhizosphere conditions. The results showed a better development of maize, especially in the aqueous soluble fraction, whose nutrient concentration was lower than that of the acid soluble fraction, as well as the organic composition. Maize growth in soils showed a better initial development in ultisol compared to oxisol, this being inferred by root:shoot biomass ratio and by scanning electron microscopy (SEM) images. However, the development of maize was better in anthropogenic soil compared to soils that received hydrochar. Conclusion: The maize growth, compared with that carried out in anthropogenic soil, suggests that during the period evaluated the addition of hydrochar in soil did not have a negative effect upon maize development in its initial phase, and could have even favoured rooting in ultisol.[Figure not available: see fulltext.]